Instalación y manejo agronómico de Lupinus mutabilis Sweet (chocho) en condiciones de tecnología media en Huarochirí, Lima - De La Cruz Pascual, Vádim Arístides (2023)
The present work called "INSTALLATION AND AGRONOMIC MANAGEMENT OF Lupinus mutabilis sweet (COCHO) UNDER MEDIUM TECHNOLOGY CONDITIONS IN HUAROCHIRI, LIMA"; It was developed at an altitude of 3,180 meters above sea level. having as genetic material or seed ecotype "cholo fuerte". The planting date of the crop was carried out on January 14 and the harvest in October 2018. The agronomic management of the crop was carried out on a 2,200-square-meter farmland. The study was aimed at the management of the "tarwi" crop, carrying out field preparation, seed treatment, planting, replanting, crop phenology, pest and disease management, irrigation, hilling, harvest and postharvest. Finally, the production costs were made. The installed crop of tarwi had a production of 390 kilograms, obtained in an area of 2200 square meters, having a yield of 1,560.00 k.ha-1, compared to the 1800.00 k.ha-1 that are considered production for said ecotype. In the costs, a total of 802.38 soles was obtained, which covered agricultural activities such as: field preparation, composting and fertilization, irrigation, pest and disease management, harvesting, land rental and purchase of inputs.